ETNOPEDAGOGIK QADRIYATLARDÍŃ TIKLENIWI – ÁDEP-IKRAM TÁRBIYASÍNÍŃ GIREWI - Pazılov, A.K. (SCIENCE and SOCIETY, 2025)
The article provides a scholarly assessment of the concept of value and provides a comparative analysis of the state and society’s approach to national values in the pre-independence period, as well as the current approach to moral education.